Leadership of Sangha Administrators in Sangha Administration at Muang District, Ratchaburi Province - (Daoruang Acaraguno), Phra Rajwallapajan (Arts of Management Journal, 2020)
A leader is one who is talented, skilled, recognized and personalized individuals who can incentivize others on the work of a group or organization to complete the objectives or goals that leaders or organizations have. Therefore, the leadership of the Monks in The District of Ratchaburi Province is a study to synthesize the study results as a data for the development of the ruling of the monks in Mueang Ratchaburi Province, and can also be a case study for other areas. Presented in related issues: 1) having foreseeable intelligence; 2) manage business with specialized expertise; and 3) have the ability to coordinate the work is completed in accordance with the period stipulated by the assessment, expecting this study to benefit the administration of the clergy.